Peran Repositori UIN Alauddin Makassar - Taufiq Mathar; Haruddin Haruddin (Literatify: Trends in Library Developments, 2021)
Institutional Repositories (IR) have been owned by many higher education institutions as a medium for the preservation, storage, and dissemination of scientific works. IR is also known as a scientific communication medium for academics/scientists. This case study describes in general the role of UIN Alauddin Makassar’s IR since it was first launched at the end of 2016 until now. The data were obtained from the experience and empirical observations of the researchers, literature review, interviews, and other supporting documentation. The results showed that the UIN Alauddin Makassar’s IR has been playing roles in; digital preservation, building scientific communication, establishing synergy between libraries and faculty communities, supporting learning and research processes, and improving library skills and services. Due to space limitations, this study does not describe in more detail the roles mentioned. This research has implications for the management of IR at this campus in particular, and other IRs in other universities.